TWO NEW SPECIES OF DORYLAIMIDA FROM MANIPUR, INDIA - DHANACHAND, CH.; RENUBALA, K.; MOHILAL, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Two new species of Dorylaimida have been described and illustrated. Xiphinemella moreanum n.sp. from soil around roots of Burmese Ing (Dipterocarpus tuberculatus Roxb.) is distinctive in having longer Oesophagus, length of odontostyle and odontophore, position of vulva, size of spicules and number of ventromedian supplements. Oostenbrinkella shamimin.sp. from soil around roots of sugarcane (Saccharum officinarum Linn.) is distinguished by its differently shaped and size of basal expanded part of oesophagus and stylet.